The tadpoles of five Megophrys Horned frogs (Amphibia: Megophryidae) from the Hoang Lien Range, Vietnam - Tapley, Benjamin; Nguyen, Luan Thanh; Cutajar, Timothy; Nguyen, Chung Thanh; Portway, Christopher; van Luong, Hao; Rowley, Jodi J. L. (Zootaxa, 2020)
Frogs in the genus Megophrys are an Asian radiation of stream-breeding frogs. The tadpoles of many Megophrys species are undescribed; those that are described are often dubiously allocated to species by association with post metamorphic specimens at collection sites and without supportive molecular data. We provide detailed descriptions of the larvae of five species of Megophrys from the Hoang Lien Range in northwest Vietnam: Megophrys fansipanensis, M. gigantica, M. hoanglienensis, M. jingdongensis and M. maosonensis. Tadpoles from different subgenera differ from each other via a combination of patternation in life, oral disc shape and tail morphology but given the small sample size, and limited number of species it is unlikely that these differences can be applied more widely to delineate subgenera. Morphological differences between tadpoles from species within the subgenus Panophrys were insufficient to clearly delineate all species. The ability to identify tadpoles is likely to advance our understanding of the frog fauna in mainland southeast Asia.